Age-Related Difference in Cognitive Performance under Severe Whole-Body Hyperthermia Parallels Cortisol and Physical Strain Responses - Junli Wang; Rima Solianik; Nerijus Eimantas; Neringa Baranauskiene; Marius Brazaitis (Medicina, 2023)
Background and Objectives: To date, understanding age-related changes in cognitive processes during heat exposure still needs to be better-understood. Thus, the main aim of the current study was to evaluate the effects of whole-body hyperthermia (WBH), i.e., a ≈ 2.5 °C increase in rectal temperature (Tre) from overnight-fast baseline value, on cognitive functioning in old and young men and to explore factors, such as stress and thermophysiological strain, that could influence such changes. Materials and Methods: Ten young (19–21 years of age) and nine old (61–80 years of age) healthy men underwent an experimental trial with passive lower-body heating in hot water immersion (HWI) at 43 °C (HWI–43 °C) until Tre reached 39 °C in old adults and 39.5 °C in young adults. Cognitive performance and cortisol concentration were assessed before and after HWI, and the physiological strain index (PSI) was assessed during HWI–43 °C. Results: PSI was lower and cortisol concentration was greater after HWI–43 °C in the old group compared with the young group (p < 0.05). Surprisingly, hyperthermia improved cognitive flexibility only in old adults, whereas short-term and visual recognition memories were maintained in both age groups. Conclusions: A ≈ 2.5 °C increase in rectal temperature can improve executive function in old adults, and this increase parallels the increased cortisol concentration and the lower thermophysiological strain under severe WBH conditions.